The effects of gender and personality on foreign language anxiety among adult multilinguals - Vasiliki Gargalianou; Katrin Muehlfeld; Diemo Urbig; Arjen van Witteloostuijn (University of Wuppertal, Schumpeter School of Business and Economics, 2015)
We investigate the relationship between gender and foreign language anxiety (FLA) in the second language (L2: English) of 320 adult bilinguals (L1: Dutch) outside the foreign language learning context. Results show that females experience higher levels of FLA. The association between gender and FLA, however, is a reflection of gender differences in personality; personality mediates most of this relationship. Individuals who are highly emotional or conscientious - dimensions for which males and females demonstrate substantial differences - experience higher levels of FLA. Furthermore, this relationship is stronger for women; that is, gender also acts as moderator to the personality-FLA relationship.
urn:nbn:de:hbz:468-20150209-151717-3
Keywords: 330; foreign language anxiety; gender; personality; survey